A National Analysis of Complications Following Total Hip Replacement in Patients With Chronic Obstructive Pulmonary Disease. Issue 12 (March 2016) - Liao, Kuang-Ming; Lu, Hsueh-Yi
Abstract : Abstract: Patients with chronic obstructive pulmonary disease (COPD) have a high risk of osteoporosis and fractures. The incidence rate of hip fracture has steadily increased over time and is a major common event in patients with osteoporosis and COPD. Total hip replacement (THR) is commonly performed in patients with hip fracture. Our aim was to compare the complications of THR between patients with and without COPD. Longitudinally linked data from the National Health Insurance Research Database, which consists of registration, claims, and reimbursement records, for a cohort of 1, 000, 000 randomly selected enrollees traced retrospectively from 1996 to 2000 in Taiwan. Patients who had undergone THR surgery between January 1, 2004, and December 31, 2008, were identified and divided into COPD and non-COPD cohorts. Outcomes and complications, including 90-day mortality, 1-year mortality, 1-year wound infection, 30-day readmission for hospitalization, 30-day pneumonia, 30-day acute respiratory failure, 30-day cerebrovascular accident, and length of stay during hospitalization, were measured after THR. The COPD group had a significantly higher ratio of complications, including 30-day readmission (14.0% vs 8.4%), 30-day pneumonia (10.4% vs 4.4%), 30-day acute respiratory failure (1.5% vs 0.5%), 1-year mortality (6.9% vs 2.7%), and length of stay in the hospital (10.6% vs 0.8%) than the non-COPD group. In addition to airway diseases, patients in the COPD group had higher mortality than those in non-COPD group after THR. Surgeons should give more attention to airway evaluation and selection of patients with COPD for THR.